Comparative effects of incretin-based therapy on doxorubicin-induced nephrotoxicity in rats: the role of SIRT1/Nrf2/NF-κB/TNF-α signaling pathways - Botros, Sandy R.; Matouk, Asmaa I.; Amin, Amr; Heeba, Gehan H. (Frontiers in Pharmacology, 2024)
Introduction: Nephrotoxicity represents a major complication of using doxorubicin (DOX) in the management of several types of cancers. Increased oxidative stress and the activation of inflammatory mediators play outstanding roles in the development of DOX-induced kidney damage. This study aimed to investigate whether the two pathways of incretin-based therapy, glucagon-like peptide-1 receptor agonist (presented as semaglutide, SEM) and dipeptidyl peptidase-4 inhibitor (presented as alogliptin, ALO), differentially protect against DOX-induced nephrotoxicity in rats and to clarify the underlying molecular mechanisms. Methods: Adult male rats were divided into six groups: control (received the vehicle), DOX (20 mg/kg, single I.P. on day 8), DOX + ALO (20 mg/kg/day, P.O. for 10 days), DOX + SEM (12 μg/kg/day, S.C. for 10 days), ALO-alone, and SEM-alone groups. At the end of the study, the animals were sacrificed and their kidney functions, oxidative stress, and inflammatory markers were assessed. Kidney sections were also subjected to histopathological examinations. Results: The co-treatment with either ALO or SEM manifested an improvement in the kidney functions, as evidenced by lower serum concentrations of creatinine, urea, and cystatin C compared to the DOX group. Lower levels of MDA, higher levels of GSH, and increased SOD activity were observed in either ALO- or SEM-treated groups than those observed in the DOX group. DOX administration resulted in decreased renal expressions of sirtuin 1 (SIRT1) and Nrf2 with increased NF-κB and TNF-α expressions, and these effects were ameliorated by treatment with either ALO or SEM. Discussion: Co-treatment with either ALO or SEM showed a renoprotective effect that was mediated by their antioxidant and anti-inflammatory effects via the SIRT1/Nrf2/NF-κB/TNF-α pathway. The fact that both pathways of the incretin-based therapy demonstrate an equally positive effect in alleviating DOX-induced renal damage is equally noteworthy.